Peningkatan Hasil Belajar Pendidikan Jasmani, Olahraga dan Kesehatan (PJOK) Materi Permainan Bola Kecil Sederhana Menggunakan Model Pembelajaran Langsung - Fahmi Razid; Ahmad Zaki Attohiri; Dadang Warta Chandra Wira Kusuma, (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study aims to improve student learning outcomes in Physical Education, Sports, and Health (PJOK) through the implementation of a direct instruction model. The research subjects were tenth-grade students of SMK Negeri 1 Masbagik in the second semester of the 2023/2024 academic year. This study employed a classroom action research (CAR) method conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. Data were collected through learning outcome tests, student activity observations, and attitude assessments. The results revealed that the systematic application of direct instruction effectively enhanced student learning outcomes in terms of cognitive, psychomotor, and affective domains. The average cognitive score increased from 63.1 in the pre-cycle to 81.17 in the second cycle. Psychomotor scores rose from 65.4 to 81.68. All students achieved 100% mastery learning by the end of the second cycle. Furthermore, there was a notable improvement in attitudes such as discipline, cooperation, and sportsmanship. Therefore, the direct instruction model can be considered an effective alternative for PJOK learning to improve both the quality of the process and the overall student outcomes.